TINDAKAN PEMERINTAH PAKISTAN TERHADAP KASUS BRIDE TRAFFICKING DI KAWASAN CHINA PAKISTAN ECONOMIC CORRIDOR (CPEC) TAHUN 2018-2019 - Ningsih, Nanda Sri Widya; Takwa, Tuah Kalti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
China Pakistan Economic Corridor (CPEC) is a collaboration officially agreed by Pakistani Prime Minister Nawaz Sharif and Chinese President Xi Jinping on April 20, 2015. For Pakistan, this collaboration is an opportunity to resolve existing challenges, such as the energy crisis, but also a golden opportunity to become a regional economic center. However, behind the expected benefits of the China Pakistan Economic Corridor (CPEC), this project has also caused serious social problems, namely cases of bride trafficking, where human trafficking involves Pakistani women who are forced to marry Chinese men and experience difficult living conditions, become victims of abuse, forced prostitution, and some are victims of organ sales in China. In this case, the study wants to find out why the Pakistani government took action to cover up the bride trafficking cases that occurred. This study uses a qualitative research method, with library research data collection techniques. Documents are sourced from books, international and national journals, official government and non-government documents, as well as news and press releases of activities. Data is also enriched with journals and official websites of the China Pakistan Economic Corridor (CPEC), and websites that are directly related to the research object. The study showed that the reason the Pakistani government covered up the bride trafficking case in the China Pakistan Economic Corridor (CPEC) project was not only an effort to protect diplomatic relations with China, but also driven by broader economic and social interests. Where these interests have a very positive impact on the country and society of Pakistan. This decision reflects the priority of the Pakistani government in pursuing economic development and social welfare, despite having to face criticism and challenges related to human rights issues. Keywords: Bride Trafficking, Cooperation, China Pakistan Economic Corridor (CPEC), Crime.